THE EFFECT OF LEADER MEMBER EXCHANGE ON EMPLOYEE JOB SATISFACTION AT PT. DUTA CAHAYA DELI MEDAN WITH PERCEIVED ORGANIZATIONAL SUPPORT AS AN INTERVENING VARIABLE - Batubara, Ayu Lestari; Sari, Ade Indah; Pitono, Pitono (Cattleya Darmaya Fortuna, 2025)
This study aims to determine the effect of leader member exchange on perceived organizational support. To determine the effect of leader member exchange and perceived organizational support on employee job satisfaction partially. To determine the effect of leader member exchange on employee job satisfaction through perceived organizational support at PT. Duta Cahaya Deli Medan. The population in this study were all employees totaling 109 people. The analysis technique used was path analysis. The results showed that leader member exchange had a positive and significant effect on employee job satisfaction, perceived organizational support had a positive and significant effect on employee job satisfaction, leader member exchange had a positive and significant effect on perceived organizational support, perceived organizational support did not mediate the effect of leader member exchange on employee job satisfaction.